Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik Menggunakan Metode WP Pada PT. Steadfast Marine, Pontianak - Deliana Sianipar; Hendri Hendri (Computer Science (CO-SCIENCE), 2023)
The best employees have the potential to increase a company's productivity, which in turn increases profits. However, the problem with PT. Steadfast Marine, a Pontianak-based company that designs and builds ships, has not done the best job of hiring the best employees. Therefore, human resource management, namely using the weighted product (WP) method to select the best employees and improve employee performance in order to remain competitive in the business world, is an important component of successful business operations. Using multiplication to relate the value of the criteria, where each criterion must be raised to the first rank, with the weight of the relevant criteria, taking into account the criteria and weights. To select the best employees accurately and computerized, DSS can help provide solutions. Research was conducted to see and prove the truth and develop pre-existing knowledge by using criteria and applying them to web applications. The employee who was selected as the best employee among the alternatives in the company can be seen from the calculation results. Leading the administration of selecting the best employees. The highest score of 0.0490 as an employee eligible for an award from the company was obtained on behalf of Sau Kong.